2017
DOI: 10.5902/1983465926726
|View full text |Cite
|
Sign up to set email alerts
|

Construção e validação de um Instrumento de Avaliação dos Fatores Críticos em Projetos de Desenvolvimento de Software.

Abstract: A necessidade de que os Sistemas de Informações (SI) apresentem disponibilidade e confiabilidade obriga que o software, como componente destes sistemas, também possua estas características. Grande parte dos trabalhos, relacionados ao tema de fatores críticos em projetos de desenvolvimento de software, utilizam a survey research (pesquisa de levantamento). Metodologia esta que, partindo de uma amostra e, através da utilização de questionários como instrumento de medição, busca descobrir as relações entre variáv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…It is suggested that this factor arises as a result of the management of the cloud environment through contracts (Wang et al , 2016). On the other hand, the CSFs change management (P17), risk management (P16), conflict of interest management (P7) and communication (P18) are not evidenced in the work of Chow and Cao (2008) but are present in the CSF literature in Fortune and White (2006), Martins Muller and Dal Forno (2017) and Stevenson and Starkweather (2017). It is also noteworthy that the dimension that encompasses CSFs related to projects loses importance for cloud projects [which differs from what was found by Chow and Cao (2008)], whereas the dimensions team management , organizational and people stand out.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…It is suggested that this factor arises as a result of the management of the cloud environment through contracts (Wang et al , 2016). On the other hand, the CSFs change management (P17), risk management (P16), conflict of interest management (P7) and communication (P18) are not evidenced in the work of Chow and Cao (2008) but are present in the CSF literature in Fortune and White (2006), Martins Muller and Dal Forno (2017) and Stevenson and Starkweather (2017). It is also noteworthy that the dimension that encompasses CSFs related to projects loses importance for cloud projects [which differs from what was found by Chow and Cao (2008)], whereas the dimensions team management , organizational and people stand out.…”
Section: Resultsmentioning
confidence: 99%
“…It is suggested that this factor arises as a result of the management of the cloud environment through contracts (Wang et al, 2016). On the other hand, the CSFs change management (P17), risk management (P16), conflict of interest management (P7) and communication (P18) are not evidenced in the work of Chow and Cao (2008) but are present in the CSF literature in Fortune andWhite (2006), Martins Muller andDal Forno (2017) and Stevenson and Starkweather (2017). It is also noteworthy…”
Section: General Analysis Of Propositions and Discussionmentioning
confidence: 99%
See 2 more Smart Citations